The nature of the knowledge acquisition process trainers use to achieve content expertise - Johnson, Daniel P. (Kansas State University, 2005)
Eduard Lindeman (1926) stated, “the approach to adult education will be via the route of situations” (p. 8, emphasis in original). Training professionals often face situations that require them to develop and present training programs on subjects for which they have limited or no previous content expertise. This occurs even though the literature stresses the need for trainers to be experts or masters on the material they present (Bernthal et al., 2004; Brookfield, 1990; Draves, 1984, 2000; Galbraith, 1990; Houle, 1984; Long, 2002; McArdle, 1993; McCain, 1999; Slusarski, 1994; Symonds, 1968; Wlodkowski, 1999). Although there is considerable literature on the roles and responsibilities of trainers (McLagan & Suhadolnik, 1989; Nadler & Nadler, 1989), self-directed learning (Candy, 1991; Knowles, 1975; Tough, 1979), and developing training programs (Caffarella, 2002; Long, 1983; McCain, 1999), very little links these areas with the knowledge acquisition process trainers use. This dissertation describes the phenomenological inquiry into the nature of the process trainers use to acquire the knowledge necessary to develop and present training programs for which they have little or no previous content expertise. The population was selected because of the researcher’s background in training and adult education. Criterion, snowball, convenience, and maximum variation purposeful sampling techniques were used to identify trainers who met the criterion of the study. Potential participants were contacted by the researcher and asked to participate in the study. Data was collected via semistructured interviews until thematic saturation was reached. Constant comparison was used to analyze the transcripts of the interviews. Twenty-six common themes were identified during the study and were categorized into six different categories. The six categories are self-directed learning, the training and development process becomes part of the trainer’s life, the needs assessment is part of knowledge acquisition, knowledge acquisition is a continuous part of the trainer’s life, understanding the importance of adult learning principles, and reflection. The results of this study have implications for the adult education, self-directed learning, program planning, human resource development, and training literature.
Keywords: Training; Program planning; Knowledge acquisition; Self-directed learning; Teaching; Learning process; Education, Adult and Continuing (0516); Speech Communication (0459)